1997
DOI: 10.1111/j.1949-8594.1997.tb17336.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Teachers and Schooling on the Vocational Choice of University Research Scientists

Abstract: Thirty‐five research scientists from the academic areas of Chemistry, Geology, Physics and Zoology were surveyed to obtain information regarding the effect of teachers and formal schooling on their decisions to become scientists. All subjects included in the study held the PhD. degree and were actively involved in research. Data analysis indicated that 63 percent of the subjects had identified a genuine interest in science by the time they were in the ninth grade, but only 9 percent of them attributed this int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Low enrolment in physics has been linked to factors such as attitudes toward and emotional connections to physics (Fischer & Horstendahl, 1997; Nashon & Nielsen, 2007; Rowsey, 1997). And, studies among African and First Nations students in Canada have revealed that scientific and alternative frameworks can coexist, a phenomenon Jegede (1995, 1996) and Aikenhead and Jegede (1999) called collateral learning.…”
Section: Resultsmentioning
confidence: 99%
“…Low enrolment in physics has been linked to factors such as attitudes toward and emotional connections to physics (Fischer & Horstendahl, 1997; Nashon & Nielsen, 2007; Rowsey, 1997). And, studies among African and First Nations students in Canada have revealed that scientific and alternative frameworks can coexist, a phenomenon Jegede (1995, 1996) and Aikenhead and Jegede (1999) called collateral learning.…”
Section: Resultsmentioning
confidence: 99%
“…Girls are then encouraged, on the basis of these stereotypes, to pursue traditionally female studies instead of mathematics, science, and other traditionally male subject areas (Carr, Jessup and Fuller; and women are steered toward certain occupations (Glick, Wilk and Perrault, 1995, Rowsey, 1997, Deaux and LaFrance, 1998. Another claim about stereotypes is that beliefs are manifested through teachers' evaluation of students (Fennema, 1990;AAUW, 1992;Jacob and Eccles, 1992;Ben-Zvi Mayer et al, 1995;Hilderbrand, 1996).…”
Section: Introductionmentioning
confidence: 99%